Microflow imaging of contrast-enhanced ultrasound for evaluation of neovascularization in peripheral lung cancer. Issue 32 (August 2016) - Wang, Song; Yang, Wei; Fu, Jing-Jing; Sun, Yu; Zhang, Hui; Bai, Jing; Chen, Min-Hua; Yan, Kun
Abstract : Abstract: The aim of this study was to investigate the role of microflow imaging (MFI) of contrast-enhanced ultrasound (CEUS) for evaluating microvascular architecture of different types of peripheral lung cancer (PLC) and to explore the correlated pathological basis. Ninety-five patients with PLC were enrolled in this study. Two radiologists independently evaluated the microvascular architecture of PLC with MFI. The interobserver agreement was measured with Kappa test. The diagnosis value of MFI was calculated. With pathological analysis, the correlation between MFI and microvascular density (MVD)/microvascular diameter (MD) was evaluated. Of the 95 PLCs, MFI were mainly classified "dead wood" (27.4%, 25.3%), "vascular" (47.4%, 49.5%), and "cotton" (20.0%, 20.0%) patterns by the 2 readers. Kappa test showed a good agreement between the 2 readers (Kappa = 0.758). The "dead wood" can be regarded as a specific diagnostic factor for squamous carcinoma; the sensitivity, specificity, and accuracy was 62.9%, 93.3%, and 82.1%, respectively. The "vascular" and "cotton" patterns correlated well with adenocarcinoma and SCLC (small cell lung cancer); diagnostic sensitivity, specificity, and accuracy were 86.7%, 65.7%, and 78.9%, respectively. MVD of "dead wood" was lower than "vascular" and "cotton, " while MD was bigger than the other 2 patterns ( P < 0.05). There was a good correlation between MFI and histopathological types of PLC as well as between MFI and MVD/MD ( P < 0.05). MFI has the advantage to display the microvascular architecture of PLCs and might become a promising diagnostic method of histopathological types of PLC. MFI features also correlated well with its pathological basis, including MVD and MD.